Functional deletion of α7 nicotinic acetylcholine receptor impairs Ca2+-dependent glutamatergic synaptic transmission by affecting both presynaptic and postsynaptic protein expression and function - Cannata, Beatrice; Sposito, Laura; Albini, Martina; Aceto, Giuseppe; Puliatti, Giulia; Lazzarino, Giacomo; Ripoli, Cristian; Tropea, Maria Rosaria; Puzzo, Daniela; Piacentini, Roberto; Grassi, Claudio (Frontiers in Physiology, 2025)
Alpha7 nicotinic acetylcholine receptors (α7-nAChRs) are ionotropic, Ca2+-permeable receptors highly expressed in brain regions involved in memory formation, such as the hippocampus. Their activation induces cation influx and neuronal depolarization, which in turn promotes glutamate release—highlighting a crucial interplay between cholinergic and glutamatergic signaling in the healthy brain. Interestingly, the genetic deletion of α7-nAChRs in mice (α7-KO mice) leads to an Alzheimer’s disease (AD)-like phenotype characterized by aberrant amyloid-β accumulation, tau phosphorylation, and neuroinflammation in aged (>12 months) mice. However, glutamatergic transmission in these mice prior to the onset of the AD-like phenotype has been poorly investigated. We thus studied molecular and functional properties of glutamatergic transmission in 4–6-months-old α7-KO mice, representing a prodromal phase of the AD-like neuropathology. We found that hippocampal CA1 neurons in brain slices from α7-KO mice showed a reduced frequency of the spontaneous excitatory post-synaptic currents (sEPSCs) compared to those of wild-type (WT) mice. On the contrary, the amplitude of sEPSCs was not affected, although in α7-KO neurons these currents displayed a longer rise time than in wild-type. CA1 neurons from α7-KO mice also exhibited a significantly smaller evoked NMDA currents than WT neurons, whereas AMPA currents were unaffected. From a molecular point of view, hippocampal neurons of α7-KO mice exhibited an increased expression of the pre-synaptic protein Synapsin-1 and of the NMDA subunits GluN2A and GluN2B, but no modifications in the expression of AMPA receptor subunits (GluA1 and GluA2) were found. Importantly, selective re-expression of the α7-nAChRs in neurons of α7-KO mice restored the evoked NMDA current amplitude and the rise time of sEPSCs, but it did not rescue the frequency of sEPSCs, thus suggesting that post-synaptic integrity depends on neuronal α7-nAChRs.